Impaired Trafficking of β1 Subunits Inhibits BK Channels in Cerebral Arteries of Hypertensive Rats. Issue 3 (September 2018) - Leo, M. Dennis; Zhai, Xue; Yin, Wen; Jaggar, Jonathan H.
Abstract : Hypertension is a risk factor for cerebrovascular diseases, including stroke and dementia. During hypertension, arteries become constricted and are less responsive to vasodilators, including nitric oxide (NO). The regulation of arterial contractility by smooth muscle cell (myocyte) large-conductance calcium (Ca 2+ )-activated potassium (BK) channels is altered during hypertension, although mechanisms involved are unclear. We tested the hypothesis that dysfunctional trafficking of pore-forming BK channel (BKα) and auxiliary β1 subunits contributes to changes in cerebral artery contractility of stroke-prone spontaneously hypertensive rats (SP-SHRs). Our data indicate that the amounts of total and surface BKα and β1 proteins are similar in unstimulated arteries of age-matched SP-SHRs and normotensive Wistar-Kyoto rats. In contrast, stimulated surface-trafficking of β1 subunits by NO or membrane depolarization is inhibited in SP-SHR myocytes. PKCα (protein kinase C α) and PKCβII total protein and activity were both higher in SP-SHR than in Wistar-Kyoto rat arteries. NO or depolarization robustly activated Rab11, a small trafficking GTPase, in Wistar-Kyoto rat arteries but weakly activated Rab11 in SP-SHRs. Bisindolylmaleimide, a PKC inhibitor, and overexpression of a PKC phosphorylation-deficient Rab11A mutant (Rab11A S177A) restored stimulated β1 subunit surface-trafficking in SP-SHR myocytes. BK channel activation by NO was inhibited in SP-SHR myocytes and restored by Rab11A S177A expression. Vasodilation to NO and lithocholate, a BKα/β1 channel activator, was inhibited in pressurized SP-SHR arteries and reestablished by bisindolylmaleimide. In summary, data indicate that spontaneously active PKC inhibits Rab11A-mediated β1 subunit trafficking in arterial myocytes of SP-SHRs, leading to dysfunctional NO-induced BK channel activation and vasodilation.